Interpersonal Communication Model of Breadwinner Moms in Building a Harmonious Household in Bandar Klippa Village, Percut Sei Tuan Subdristrict, Deli Serdang Regency, North Sumatera, Indonesia - Anggraini, Qorry; Mazdalifah; Nurbani (Indonesian Journal of Advanced Research, 2024)
This research aims to analyze the communication process, role exchange, and interpersonal communication model of breadwinner mothers in building a harmonious household in Bandar Klippa Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, Indonesia. The method used in this research is a descriptive method with a qualitative approach so that the data is then explained in sentence form. Researchers used interviews and documentation techniques to collect data from informants and triangulation. The results found by researchers include that the communication process continues because there is an element of mutual love and need for each other, the exchange of roles that occurs is contrary to functional structure and cultural norms, so the word "boru" appears. For Batak husbands who help with household work, the communication model that occurs is the Schramm model combined with the theory of the division of roles and needs from the discipline of psychology.